Pola Pemberdayaan Desa Sejahtera Astra (DSA) pada Petani Kopi Robusta di Desa Muncar Kecamatan Gemawang Kabupaten Temanggung - Try Feby Wulandari; Dimas Deworo Puruhito; Istiti Purwandari (Program Studi Agribisnis INSTIPER Yogyakarta, 2023)
This study aims to determine the pattern of empowerment of DSA (Desa Sejahtera Astra) in providing training, facilities and infrastructure, and marketing of coffee products in Muncar Village, Gemawang District, Temanggung Regency. This research was conducted from 1 to 31 July 2022. This research was conducted using a qualitative descriptive method. The sampling method is done by census or total sampling, which is a sampling technique with all members of the population being sampled. Respondents in this study amounted to 23 people. The results showed that the empowerment carried out by DSA in providing training included training in the use of post-harvest processing equipment and training in packaging coffee products; provision of facilities and infrastructure in the form of post-harvest processing equipment such as: coffee skin peeler, grinding machine, roasting machine, sealer machine, all of which are placed in a yield processing unit (UPH); and marketing training through Tourism Villages.